1986
DOI: 10.1042/bj2390147
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopy of cervical, gastric and bronchial mucus glycoproteins

Abstract: Mucus glycoproteins (mucins) were obtained from human cervical and pig gastric mucus as well as from chronic-bronchitic sputum after low-shear extraction. The mucus gel was solubilized in guanidinium chloride supplemented with proteinase inhibitors, and the macromolecules were purified by using isopycnic density-gradient centrifugation. The macromolecules were spread in monolayers of benzyldimethylalkyl-ammonium chloride and studied with electron microscopy after staining with uranyl acetate and/or shadowing w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
101
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(112 citation statements)
references
References 17 publications
11
101
0
Order By: Relevance
“…The images were selected at random and are representative of a large library of images, which portray similar structural information and surface coverage. The PGM appears as long filamentous strands, which is in good agreement with previous studies using electron and scanning tunnelling microscopy [18][19][20][21], and consistent with the swollen coil array\linear random coil model for mucins [4,23]. The characteristic flattened areas along the backbone seen earlier from electron microscopy for PGM and earlier for bronchial mucins [23] were notably absent.…”
Section: Pgm Glycoproteinsupporting
confidence: 90%
See 2 more Smart Citations
“…The images were selected at random and are representative of a large library of images, which portray similar structural information and surface coverage. The PGM appears as long filamentous strands, which is in good agreement with previous studies using electron and scanning tunnelling microscopy [18][19][20][21], and consistent with the swollen coil array\linear random coil model for mucins [4,23]. The characteristic flattened areas along the backbone seen earlier from electron microscopy for PGM and earlier for bronchial mucins [23] were notably absent.…”
Section: Pgm Glycoproteinsupporting
confidence: 90%
“…In order to reveal both the thin filamentous nature of the gastric mucin structure previously shown with transmission electron [ [18][19][20] and scanning tunnelling microscopy [21], together with the previously unvisualized characteristics of chitosan, an extremely flat sample substrate is required. To this end, mica was chosen for this study.…”
Section: Control Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies of PGM concluded that its general structure and chemical composition are similar to those of human gastric and respiratory mucins (Boat et al, 1976b;Scawen & Allen, 1977;Sheehan et al, 1986). However, more recent studies of mucins from a variety of species and epithelial locations have highlighted differences both between individual mucins and within overall mucus composition and this is reflected in the results obtained here and in previous studies on Pseudomonas mucin desulfation (Jansen et al, 1999;Tralau et al, 2007).…”
Section: Discussionsupporting
confidence: 50%
“…Mucins are long, flexible and highly glycosylated proteins, with a fiber diameter of 5-10 nm based on their biochemical structure and as confirmed by both negatively stained electron microscopic images of individual mucin fibers (22,23) and by the DMSOmediated glutaraldehyde fixation method (1). The concentration of mucins in mucus gels typically ranges between 1-5% (1,(24)(25)(26)(27)(28).…”
Section: Resultsmentioning
confidence: 99%